Factors Affecting Preadolescence Student Online Learning Anxiety During the COVID-19 Pandemic - Viriyaporn Tapsuri,; Titiworada Polyiem, (Journal of Educational Issues, 2024)
The current study aims to investigate factors affecting the online learning anxiety of preadolescent learners during COVID-19 prevention policy. The study was designed with a survey approach. The participants were 181 grade 6 students in a public school in Thailand selected by Yamane’s sampling method. During the data collection, Thai educational institutions were politicized to be online. The school was in a suburban area of a small province in Thailand. Therefore, the samples were from lower-middle income families and have problems with devices and the internet signal. Classes were held via online conferencing platforms such as Google Meet and Zoom, and exercises were assigned both online and in textbooks. The instrument was a questionnaire designed to assess the online learning anxiety of preadolescent learners during COVID-19 prevention policy. The data were gathered at the end of the 2021 academic year when all classes were instructed online due to COVID-19 prevention policy. The data were analyzed using percentages, mean scores, standard deviation, and thematic analysis. The results of the study that instructional factors affect preadolescent learners’ online learning anxiety during the COVID-19 pandemic. The data are beneficial for teachers, policymakers, and scholars in the area of study.